2020
DOI: 10.1364/oe.406006
|View full text |Cite
|
Sign up to set email alerts
|

Broadband switchable terahertz half-/quarter-wave plate based on metal-VO2 metamaterials

Abstract: Dynamically switchable half-/quarter-wave plates have recently been the focus in the terahertz regime. Conventional design philosophy leads to multilayer metamaterials or narrowband metasurfaces. Here we propose a novel design philosophy and a VO2-metal hybrid metasurface for achieving broadband dynamically switchable half-/quarter-wave plate (HWP/QWP) based on the transition from the overdamped to the underdamped resonance. Results show that, by varying the VO2 conductivity by three orders of magnitude, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The middle layer is polyimide with the permittivity of ε = 3.5 and the loss tangle of 0.002. For the 200 nm thick VO 2 film, the insulatorto-metal transition properties of VO 2 can be described by different values of conductivity to realize the switchability of multiple functions [21,[27][28][29][30][31][32] . In our research, the conductivity of VO 2 is set as 200 S/m and 2 × 10 5 S=m to mimic insulating state and metallic state, respectively [27,31] .…”
Section: Design and Resultsmentioning
confidence: 99%
“…The middle layer is polyimide with the permittivity of ε = 3.5 and the loss tangle of 0.002. For the 200 nm thick VO 2 film, the insulatorto-metal transition properties of VO 2 can be described by different values of conductivity to realize the switchability of multiple functions [21,[27][28][29][30][31][32] . In our research, the conductivity of VO 2 is set as 200 S/m and 2 × 10 5 S=m to mimic insulating state and metallic state, respectively [27,31] .…”
Section: Design and Resultsmentioning
confidence: 99%
“…By contrast, χ = 1 means that the reflected THz wave is a typical left-hand circular polarization (LHCP) wave. When and ∆Φ ≈ 2 n π ± π ( n is an integer), the metamaterial can realize linear-to-linear polarization conversion, and its polarization conversion characteristics can be described by the polarization conversion rate and the degree of linear polarization [ 38 ]. The polarization conversion rate is defined as , and the degree of linear polarization is defined as .…”
Section: Polarization Conversion Properties Of Metamaterialsmentioning
confidence: 99%
“…[6] These two factors prevent the simultaneous achievement of orthogonal-polarization modulation and high efficiency, especially in terahertz or higher frequency regions. Although multilayer vanadium-dioxide metasurfaces have been seen as promising for use in efficient multifunctional devices, such as reconfigurable absorbers, [36][37][38][39][40][41][42][43][44][45][46][47][48] reprogrammable wavefront-engineering metasurfaces, [49,50] and devices switchable between quarterand half-wave plates, [51] these proposals have not been realized experimentally, because of the stringent fabrication challenges. Although a few studies have reported experimental realization of multilayer vanadium-dioxide structures for infrared polarization modulation [52] and terahertz asymmetric transmission, [53] they did not focus on orthogonal-polarization modulation.…”
Section: Introductionmentioning
confidence: 99%